Performance Analysis of Digital Modulation for Coherent Detection of OFDM Scheme on Radio over Fiber System - Fauza Khair; Fakhriy Hario P; I Wayan Mustika; Budi Setiyanto (Institute of Advanced Engineering and Science, 2016)
Radio over fiber (RoF) system with the coherent detection offers high linearity for the transparent transport of high-frequency microwave signals, and better receiver sensitivity compared with intensity-modulated direct detection systems. The purpose of this paper is to analyze the performance of digital modulation for coherent detection of orthogonal frequency division multiplexing (OFDM) scheme on RoF system at 10 Gbps up to 100 km fiber length. The results show that coherent detection of OFDM-RoF system with 16 quadrature amplitude modulation (16-QAM) has the value of bit error rate (BER) and the symbol error rate (SER) is very low and its constellation is better compared with other modulation formats (4-QAM, quadrature phase shift keying (QPSK), 8-PSK and 16-PSK), which BER 16-QAM is 0.053 and SER is 15.7%. The results also show that BER value of 4-QAM and QPSK relatively similar to fiber length variations. In general, an increasing value of the BER and SER for each modulation format are almost equal to the fiber length of 60-70 km (Region I and II). However, there is a significant increase in the value of BER in fiber length of 80-100 km (Region III. A and III. B) for the modulation of 4-QAM, QPSK, 8-PSK, and 16-PSK.